Impact of NCI-MATCH: a Nationwide Oncology Precision Medicine Trial. Issue 4 (4th July 2019) - Khan, Sabrina S.; Chen, Alice P.; Takebe, Naoko
ABSTRACT: Introduction : The National Cancer Institute-Molecular Analysis for Therapy Choice (NCI-MATCH) is a multicenter phase II tissue agnostic trial with 39 treatment arms, that matches a targeted drug to an actionable genetic alteration identified by next-generation sequencing (NGS). It is unique in use of a bioinformatics tool MATCHBox to make patient treatment assignments. The purpose of this review is to offer an update on the current status of NCI-MATCH, and also to discuss the impact of this precision medicine trial on future studies. Areas covered : This review discusses how NCI-MATCH has evolved over time to address the challenges in enrollment as well as to better answer the needs of the wider cancer community. The interim results from the available arms are described, together with a discussion on the future direction of NCI-MATCH. Expert opinion : The NCI-MATCH is generating a unique genetic mutation landscape of relapsed/refractory malignancies, on top of which the future of precision medicine will be built upon. Real-time updates to public databases with new genetic alterations can further optimize treatment assignments for cancer patients. Formation of more definitive trials can study any promising treatments discovered.